Assessments Regarding the Regulation of the Electricity Distribution Market - Cuentas Anci, Hernán (2007)
After establishing the need for regulation on natural monopolies, the author describes some aspects of the electricity distribution sector and criticizes the limitations of the current model used by regulators to measure their performance, and concludes by proposing an alternative approach.